Cost benefit analysis of clinical pharmacist interventions in medical intensive care unit in Palestine medical complex: Prospective interventional study - Aseel Houso; Motasem Hamdan; Hiba Falana (Elsevier, 2022)
Background: Clinical pharmacy services in the critical health care settings have expanded dramatically.Study problem.Clinical pharmacy services have limited implementation in Palestine. Many intensive care units (ICUs) patients do not get the intended beneficial effects of their treatment due to treatment related problems and their consequent cost burden. Aim: To evaluate the impact of the clinical pharmacist interventions on costs of care and safety of patient by assessing treatment related problems among medical ICUs patients in Palestine. Methodology: A prospective interventional study was conducted at medical ICU of the major public hospital in Ramallah city over a 4-month period (between September and December 2020). Patients were randomly assigned to either an intervention or a control group (With / without clinical pharmacist involvement). Treatment related problems were identified in both study groups by the clinical pharmacist, but interventions were only provided to the intervention group. The total economic benefit included both cost savings from intervention and cost avoidance from preventable adverse drug events (ADEs) resulted from CP interventions. The primary outcomes with the clinical pharmacist interventions were net benefit and benefit to cost ratio, which were calculated using previously published methodologies and adjusted to the Palestinian settings. The analysis of CP interventions acceptance by physicians was performed. Results: During the 4-month study period, the 117 patients admitted to the ICU were included into the analysis; 66 patients in the intervention group and 51 in the control group. The interventions made by a clinical pharmacist resulted in direct cost saving of NIS8,990.05 ($2799.63) and cost avoidance of NIS22,087.5 ($ 6878.37). Translated into a net savings of NIS188.35 ($58.65) per intervention and NIS470 ($146.36) per patient. Comparison of benefits (NIS31,077.55) ($9678.00) and costs (NIS19,043.928) ($5930.55) indicate a net economic benefit to the institution of (NIS 12,033.623) ($3747.44) and a benefit cost ratio of 1.63. Conclusion: Integrating a clinical pharmacist in the ICU team was investment that resulted in benefits in term of cost saving and cost avoidance.